Magneto- and Tensoresistance of the p Ge Compensated Crystals in the Range of Weak, Intermediate and Classically Strong Magnetic Fields - Gaidar, G.P. (Physics and Chemistry of Solid State, 2016)
On the crystalsof compensatedp‑Ge (with the compensation factor of k = NSb/NGa = 0.5) the transverse (Н ^ (J // X)) magnetoresistance (within the magnetic fields of 0 < Н £ 22.3 kOe) at fixed values of the mechanical stresses Хі = 0; 0.2; 0.4; 0.6; 0.9; 1.1; 1.5 GPa were measured at 77 K. These mechanical stresses X created the elastic deformation along the samples, the crystallographic orientation of which coincided with the direction of [100]. Also at fixed magnetic field intensities Ні = 2; 4; 8; 10; 15; 20; 22.3 kOe the dependencies of resistivity on the mechanical stress X, which coincides with the longitudinal axis of the crystal (X // J // [100]) and changes in the range of 0 £ Х £ 1.5 GPa, were measured. Last dependences characterized by the presence of a minimum in the range of X 0.5 ¸ 0.6 GPa at the minimal magnetic field intensities Н = 2 kOe, which was shifted to the values of X 0.2 ¸ 0.3 GPa with increasing Н up to 22.3 kOe.